Brain energy failure in dementia syndromes: Opportunities and challenges for glucagon‐like peptide‐1 receptor agonists. Issue 3 (14th October 2021) - Yassine, Hussein N.; Solomon, Victoria; Thakral, Angad; Sheikh‐Bahaei, Nasim; Chui, Helena C.; Braskie, Meredith N.; Schneider, Lon. S.; Talbot, Konrad
Abstract: Medications for type 2 diabetes (T2DM) offer a promising path for discovery and development of effective interventions for dementia syndromes. A common feature of dementia syndromes is an energy failure due to reduced energy supply to neurons and is associated with synaptic loss and results in cognitive decline and behavioral changes. Among diabetes medications, glucagon‐like peptide‐1 (GLP‐1) receptor agonists (RAs) promote protective effects on vascular, microglial, and neuronal functions. In this review, we present evidence from animal models, imaging studies, and clinical trials that support developing GLP‐1 RAs for dementia syndromes. The review examines how changes in brain energy metabolism differ in conditions of insulin resistance and T2DM from dementia and underscores the challenges that arise from the heterogeneity of dementia syndromes. The development of GLP‐1 RAs as dementia therapies requires a deeper understanding of the regional changes in brain energy homeostasis guided by novel imaging biomarkers.